Masa Kepemimpinan Khalifah Umar Bin Khattab - Tiara Putri Rizkia; Muhammad Ricky Hardiyansyah (Medan Resource Center, 2022)
This article aims to discuss the position of Umar Bin Khattab as the second Caliph of Muslims after the death of the Prophet Muhammad SAW. He reigned for about 10 years. Various achievements were achieved at the peak of his leadership. This research uses historical research methods with literature study. A leader who is brave, hardworking, wise and has a gentle attitude. The success of Umar ibn al-Khattab in leading the Muslim community at that time proved that he was a reliable person in the field of state administration. Umar ibn al-Khattab was the second caliph after Abu Bakr as-Siddiq who was successful in carrying out the mandate of the people in running the wheels of government. The results of the work of the Caliph Umar Bin Khattab included the caliph who was the first to call himself Amirul Mukminin, he was the first to form a kanot/ministry, then he was the first to make the Islamic calendar by making the beginning of the Prophet's migration as the beginning.